Portaratrum, a new genus of deep-sea Tanaidacea (Crustacea) with description of two new species - Guerrero-Kommritz, Jürgen (Zootaxa, 2003)
A new genus, Portaratrum n. gen. and two new species, one from the Atlantic Ocean and one from the Pacific Ocean are described. The new genus is characterized by a downwardly directed pleonal spur, cheliped basis fused to the cephalothorax, biramous uropods, pars molaris blunt with several terminal spinules. At present the genus is assigned to the family Colletteidae. Both species were collected from depths exceeding 4000 m.